Performance, carcass traits, meat quality and economic analysis of feedlot of young bulls fed oilseeds with and without supplementation of vitamin E - Machado Neto, Otávio Rodrigues [UNESP]; Ladeira, Márcio Machado; Chizzotti, Mário Luiz; Jorge, Andre Mendes [UNESP]; Oliveira, Dalton Mendes de; Carvalho, José Rodolfo Reis de; Ribeiro, Julimar do Sacramento (Sociedade Brasileira de Zootecnia, 2012)
The objective of this research was to evaluate average daily gain (ADG), carcass traits, meat tenderness and profitability of keeping cattle fed different oilseeds and vitamin E in feedlot. A total of 40 Red Norte young bulls with initial average body weight of 339±15 kg were utilized. The experimental design was completely randomized in a 2 × 2 factorial arrangement. The experiment lasted 84 days and experimental diets presented soybeans or cottonseeds as lipid sources associated or not to daily supplementation of 2,500 UI vitamin E per animal. The concentrate:roughage ratio was 60:40. Diets had the same amount of nitrogen (13% CP) and ether extract (6.5%). The data were analyzed by means of statistical software SAS 9.1. Neither vitamin supplementation nor lipid source affected ADG. There was no interaction between lipid source and vitamin supplementation for the variables studied. The inclusion of cottonseed reduced the carcass yield. There was no effect of diets on hot and cold carcass weights or prime cuts. The inclusion of cottonseed reduced the backfat thickness. No effect of experimental diets on the rib-eye area was observed. There was no effect of lipid source or vitamin supplementation on meat tenderness, which was affected, however, by ageing time. Diets with soybeans presented higher cost per animal. The utilization of soybean implied reduction of the gross margin (R$ 59.17 and R$ 60.51 for diets based on soy with and without supplemental vitamin, respectively, vs. R$ 176.42 and R$ 131.79 for diets based on cottonseed). The utilization of cottonseed enables improvement of profitability of feedlot fattening, in spite of negatively affecting some carcass characteristics.
Keywords: cottonseed; ageing; profitability; soybean